EFFECT OF PATTERN RATION WITH ADDITION OF SHRIMP WASTE AND SPINACH ON BODY WEIGHT INCREASE KAMPONG CHICKEN - Fitriani Ulfatus Saadah; Mei Sulistyoningsih (Bioma : Jurnal Ilmiah Biologi, 2011)
Chicken is one source of animal protein for humans. Chicken body weight can be used as one indicator of the amount of protein in the body of chicken. Therefore, efforts to increase body weight become very im-portant in poultry, especially kampong chickens. This study aims to determine the significance of the pattern of food ra-tions by the addition of shrimp waste and spinach to the increased weight of kampong chicken (Gallus bankiva) the most effective. The study was conducted in Semarang. The subjects were 60 chickens that are kept for eight weeks. The design used was completely ran-domized design (CRD) with four treatments and five replicates. Data analyzed by Anova. The results shows that the influence of ration patterns with the addition of shrimp waste and spinach of weight gain, which is very significant at 1% probability level. The highest mean is in D treatment (ration plus the waste of shrimp and spinach) The conclusion is, the pattern of the feed ration is very important in in-creasing kampong chicken body weight. If the pattern rations are proper, the addition of chicken body weight will reach the optimum. Waste shrimp and spinach can meet the nutritional needs of kampong chicken. Key words: kampong chicken, body weight, ration, wastes of shrimp, spinach